2019
DOI: 10.1002/hep.30404
|View full text |Cite
|
Sign up to set email alerts
|

ID3 Promotes Stem Cell Features and Predicts Chemotherapeutic Response of Intrahepatic Cholangiocarcinoma

Abstract: Cancer stem cells contribute to a high rate of recurrence and chemotherapeutic resistance in many types of cancer, including intrahepatic cholangiocarcinoma (ICC). Inhibitor of differentiation 3 (ID3) has been reported to promote cancer stem cells, but its role in ICC is obscure. In this study, we identified that ID3 is highly expressed in human ICC tissues compared with matched normal tissues and correlates with poor prognosis. Functional studies demonstrate that ID3 is required for stemness maintenance in ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 41 publications
(54 reference statements)
0
34
2
Order By: Relevance
“…A). CD133 has been consistently reported to be a marker of chemo‐resistant cancer cells, which are enriched after treatment, and CD133+ BTC cells were shown to be tumorigenic and express features of cancer stem cells (CSCs) . Therefore, we speculated that MIR1249 could affect chemo‐resistance by inducing the expansion of CD133+ BTC cells.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…A). CD133 has been consistently reported to be a marker of chemo‐resistant cancer cells, which are enriched after treatment, and CD133+ BTC cells were shown to be tumorigenic and express features of cancer stem cells (CSCs) . Therefore, we speculated that MIR1249 could affect chemo‐resistance by inducing the expansion of CD133+ BTC cells.…”
Section: Resultsmentioning
confidence: 98%
“…Several mechanisms of chemo‐resistance may act synergistically and drive cancer cells to escape biochemical inhibition or cell death caused by chemotherapy . Acquisition of stemness features in cancer cells appears to be a driver of resistance that is common with other tumor types …”
mentioning
confidence: 99%
“…Targeting EGFR with an existing therapy might be a potential strategy for EOC treatment through the eradication of CSCs. In intrahepatic cholangiocarcinoma, ID3 promotes CSCs by activating β-catenin and is correlated with poor prognosis [ 50 ]. This gene expression may be associated with OC prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, a recent study found that mitochondrial impairment activated the Wallerian pathway and caused the axon degeneration by the depletion of NMNAT2 [36]. Moreover, ID3 was reported to act as a biomarker promoting the stemness of intrahepatic cholangiocarcinoma by promoting the transcriptional activity of β-catenin [37]. Furthermore, high-grade serous ovarian carcinoma patients with higher expression of FXYD5 owned a shorter survival time than patients with lower expression of FXYD5, and FXYD5 played a critical role in survival and prognosis of HCSOC [38].…”
Section: Discussionmentioning
confidence: 99%